2011
DOI: 10.1007/s11764-011-0184-8
|View full text |Cite
|
Sign up to set email alerts
|

Exercise among breast and prostate cancer survivors—what are their barriers?

Abstract: Introduction Despite proven benefits of regular physical activity, estimates indicate that few cancer survivors meet physical activity guidelines. The purpose of this paper is to identify and compare exercise barriers among cancer survivors, both cross-sectionally and longitudinally as they undergo home-based behavioral interventions. Methods Data on a sample of 452 breast and prostate cancer survivors who completed the FRESH START trial were analyzed collectively, as well as separately by cancer-type. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
106
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 28 publications
13
106
3
1
Order By: Relevance
“…Several studies have collected exercise barrier data from cancer patients who were participating in supervised exercise intervention as part of a clinical trial, and reported that the greatest barriers to exercise are 'lack of time' or 'too busy' regardless of cancer type (Courneya et al, 2005;Ottenbacher et al, 2011). The limitation of these studies is that results from these studies could only be applied to patients who are participating in regular or scheduled exercise sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have collected exercise barrier data from cancer patients who were participating in supervised exercise intervention as part of a clinical trial, and reported that the greatest barriers to exercise are 'lack of time' or 'too busy' regardless of cancer type (Courneya et al, 2005;Ottenbacher et al, 2011). The limitation of these studies is that results from these studies could only be applied to patients who are participating in regular or scheduled exercise sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Another key concept related to intention is that of motivation or 'willpower'. Ottenbacher et al (2011) found that, of their sample of breast and prostate cancer survivors, those who reported 'no willpower' to be physically active engaged in less physical activity. Significantly, 'no willpower' was reported as a barrier by 51% of breast and 44% of prostate cancer survivors.…”
Section: Addressing Psychological Barriers To Physical Activitymentioning
confidence: 99%
“…These frequently include lack of time or being too busy, nonspecific treatment side effects, fatigue, nausea, diarrhoea, surgical complications, work or family responsibilities, and lack of enjoyment Ottenbacher et al, 2011;Rogers et al, 2008). Some of these barriers are also often reported in general population samples.…”
Section: Barriers To Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations